Measuring misaligned contraceptive use among reproductive-aged women in Kisumu, Kenya: a cross-sectional, population-based study - Ginger Golub; Leigh Senderowicz; Dickens Onyango; Katherine Tumlinson; Stephanie Chung; Emilia Goland; Brooke W. Bullington; Claire W. Rothschild; Abigael Mwanyiro; Ben Wekesa; Brian Frizzelle (BMJ Public Health, 2025)
Introduction Global family planning scholars have critiqued traditional measures of programmatic success and called for new, person-centred measures that consider people’s preferences. We propose a new measure that assesses the alignment between an individual’s contraceptive desires and use.Methods We use data from a population-based survey implemented among adult reproductive-aged women in Kisumu, Kenya. We define misaligned contraceptive use as discordance between contraceptive desires and use (ie, desire for contraception paired with non-use or no desire for contraception paired with use). We expand misaligned use to incorporate non-preferred contraceptive method use, defined as the use of a method with a preference for a different method among contraceptive users. We also compare unmet need for family planning with misaligned use.Results In our total sample, including contraceptive users and non-users, 86% of participants had aligned contraceptive use and 14% had misaligned use. Among contraceptive users, we found that 74% of participants had aligned and preferred method use, 21% had aligned and non-preferred method use, 2% had misaligned and preferred use, and 3% had misaligned and non-preferred use. Our comparison of misaligned use and unmet need showed little agreement.Conclusions Measuring misaligned and non-preferred contraceptive method use has implications for family planning measurement and programming. Our results demonstrate the importance of capturing contraceptive desires rather than assuming an implicit desire for contraception among those who do not desire pregnancy. Further, incorporating method preferences into misaligned use provides additional detail on who does and does not have their contraceptive desires met. Finally, measuring misaligned and non-preferred method use highlights subsets of populations who may benefit from additional contraceptive programming to improve contraceptive access or enable method discontinuation or switching, and therefore can be imperative to ensuring that individuals have their reproductive desires realised.